Arteriovenous malformation of head and neck: A case report - Hussain, Tahir; Farooqui, Fareeha; Jehan, Meher (Journal of the Pakistan Medical Association, 2022)
Extra-cranial arteriovenous malformations of head and neck are rare and may present with acute haemorrhage. Their management varies and requires a multidisciplinary approach. Intra-arterial embolisation alone or followed by surgery is recommended. We present here a case of a huge pulsatile lesion extending from the neck to the temporo-parietal region with the main feeding vessel being the right external carotid artery. It was treated with surgical resection only as the feeding artery was very tortuous making selective embolization of artery impossible. The excision of the portion of the artery in the neck was carried out a week later. The patient recovered smoothly except for transient facial nerve palsy. Keywords: arteriovenous malformation, vascular anomalies, CT angiogram. Continuous...